2022
DOI: 10.1111/iji.12577
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Rh and K phenotypes among blood donors from different ethnicities in Samtah (Southwestern Region) Saudi Arabia

Abstract: Introduction: Rh and Kell blood group systems are amongst the most important blood group systems; being highly immunogenic after ABO system. The aim of this study was to evaluate the frequencies of Rh antigens, haplotypes and K antigen among blood donors belonging to various ethnicities in Samtah, Jazan, Saudi Arabia.Methods: This study was conducted during January 2019 and August 2020 at Samtah General Hospital, Samtah. Records of all blood donors recruited during this period were included for data acquisitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Same as RhD, the RHCE*C is found to be higher (76%) in our population study visive Caucasian population which is around 68% [17,24]. Other populations studies done in China [17,18], India [25, 26,27,28] and UAE [29,30,31] reported a C antigen percentage of around 93, 87 and 73 respectively. RHCE*C is more commonly found in D positive individuals than RhD negatives.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Same as RhD, the RHCE*C is found to be higher (76%) in our population study visive Caucasian population which is around 68% [17,24]. Other populations studies done in China [17,18], India [25, 26,27,28] and UAE [29,30,31] reported a C antigen percentage of around 93, 87 and 73 respectively. RHCE*C is more commonly found in D positive individuals than RhD negatives.…”
Section: Discussionsupporting
confidence: 50%
“…E allele is the least prevalent (22.96%) which is similar to other studies from around the world such as in India [25, 15,26,16,27], Pakistan [26], Oman [29] , , Southern Eastern Europe [1] and others. Interestingly, studies done in China reported a higher prevalence of E antigen (39%) [30]. Further to that studies done on the population in Mainland China reported even a higher prevalence of 51% [29].…”
Section: Standard Colour Scheme Of Haploview Was Applied For Linkage ...mentioning
confidence: 90%
“…For the last 15 years, and to minimise the risk of alloimmunisation, the recommended transfusion protocol for patients with SCD or Thalassemia in the region has been the selection of RBC units that are extended-phenotype-matched for RhC, E, c, e, and K antigens, in addition to the standard matching for ABO and RhD types. 19 Furthermore, a recent study by Alsughayyir et al (2022) reported a gap between blood supply and the increased demand for blood for daily routine and emergency practices. 20 Despite this fact, there was only one study investigating the effect of this practice on the prevalence and nature of alloimmunisation among these groups of patients 21 in this endemic area of hemoglobinopathies.…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition, it should be mentioned that a recent study reported that 55% of blood donors were Saudi and 45% otherwise among 4977 blood donors in Samtah-Jazan, which might impact the rate of alloimmunization in the region. 19,22 Furthermore, the incidence of A2 and A2B subgroups and anti-A1 antibody in the region has been linked to possible complications. 23 Hence, we sought to look the rate of alloimmunisation in SCD and thalassemia patients in different hospitals of Jazan region, thus will provide in depth data for the improvement of blood transfusion protocol among SCD and thalassemia and report the finding to health care provided for more attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation